Organic functionalized Fe3O4/RGO nanocomposites for CO2 adsorption. Issue 3 (June 2017) - Babu, C.M.; Vinodh, R.; Selvamani, A.; Kumar, K. Prathap; Parveen, A. Shakila; Thirukumaran, P.; Srinivasan, V.V.; Balasubramaniam, R.; Ramkumar, V.
Graphical abstract: Abstract: The core-shell Fe3 O4 @SiO2 nanoparticles were functionalized on their surface with (3-aminopropyl)triethoxysilane and then crosslinked with 1, 2-dibromoethane to obtain 1, 2-dibromoethane crosslinked aminefunctionalized ironoxide nanoparticles (organic functionalized nanoparticles). Graphene oxide was synthesized by modified Hummer's method and then reduced with hydrazine hydrate to obtain reduced graphene oxide. The synthesized organic functionalized nanoparticles were dispersed on to the reduced graphene oxide to obtain reduced graphene oxide nanocomposites. The nanocomposites were characterized by using XRD, FT-IR, TGA, N2 adsorption, SEM and TEM. The influence of textural properties of these nanocomposites over the CO2 adsorption behaviour was investigated. The nanocomposites showed high surface area of 423 m 2 /g with high porosity. This is due to the fine dispersion of the organic functionalized nanoparticles on to the reduced graphene oxide. These nanocomposites are used for CO2 adsorption showing high adsorption capacity of 6.9%.